1995
DOI: 10.1002/mrdd.1410010305
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to opiates

Abstract: Opiate use has been described for thousands of years. In this century, clinical features of the “neonatal abstinence syndrome” have been amply documented in the medical literature. Indeed, the abuse of “recreational” drugs continues at an alarming rate and results in a high number of adverse maternal‐fetal outcomes even as we near the end of the twentieth century. These consequences persist despite the myriad of medical advances that have resulted in the lowest perinatal mortality on record. The effects of opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The high prevalence of prematurity, microcephaly, and hypertonia reported here has been previously described for children exposed in utero to heroin or cocaine or both. [5][6][7][8] Of the 93 women who volunteered birth histories, 40 self-reported illicit drug use during pregnancy. Dysmorphic features of a diverse nature were seen in 10% of the children evaluated, although only 4% followed a pattern associated with a described syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high prevalence of prematurity, microcephaly, and hypertonia reported here has been previously described for children exposed in utero to heroin or cocaine or both. [5][6][7][8] Of the 93 women who volunteered birth histories, 40 self-reported illicit drug use during pregnancy. Dysmorphic features of a diverse nature were seen in 10% of the children evaluated, although only 4% followed a pattern associated with a described syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that needle exchange programs do not increase rates of drug use 6 or increase numbers of discarded needles or syringes 7 ; because drug use has been associated with crime, 8,9 however, there are concerns that crime rates may increase in areas surrounding needle exchange programs after their introduction.…”
mentioning
confidence: 99%